XAS/DRIFTS/MS spectroscopy for time‐resolved operando investigations at high temperature. (23rd October 2018) - Agostini, G.; Meira, D.; Monte, M.; Vitoux, H.; Iglesias-Juez, A.; Fernández-García, M.; Mathon, O.; Meunier, F.; Berruyer, G.; Perrin, F.; Pasternak, S.; Mairs, T.; et al.
Abstract : A new reactor cell and experimental setup designed to perform time‐resolved experiments on heterogeneous catalysts under working conditions that simulltaneously combines XAS, DRIFT and MS spectroscopies are reported. Abstract : The combination of complementary techniques in the characterization of catalysts under working conditions is a very powerful tool for an accurate and in‐depth comprehension of the system investigated. In particular, X‐ray absorption spectroscopy (XAS) coupled with diffuse reflectance infrared Fourier transform spectroscopy( DRIFTS) and mass spectroscopy (MS) is a powerful combination since XAS characterizes the main elements of the catalytic system (selecting the absorption edge) and DRIFTS monitors surface adsorbates while MS enables product identification and quantification. In the present manuscript, a new reactor cell and an experimental setup optimized to perform time‐resolved experiments on heterogeneous catalysts under working conditions are reported. A key feature of this setup is the possibility to work at high temperature and pressure, with a small cell dead volume. To demonstrate these capabilities, performance tests with and without X‐rays are performed. The effective temperature at the sample surface, the speed to purge the gas volume inside the cell and catalytic activity have been evaluated to demonstrate the reliability and usefulness of the cell. The setup capability of combining XAS, DRIFTS and MS spectroscopies is demonstrated in a time‐resolved experiment, following the reduction of NO by Rh nanoparticles supported on alumina.